Diagonal block method for solving two-point boundary value problems with Robin boundary conditions - Nadirah, Mohd Nasir; Zanariah, Abdul Majid; Fudziah, Ismail; Norfifah, Bachok (Hindawi Publishing Corporation, 2018)
This numerical study presents the diagonal block method of order four for solving the second-order boundary value problems (BVPs)with Robin boundary conditions at two-point concurrently using constant step size. The solution is obtained directly without reducing to a system of first-order differential equations using a combination of predictor-corrector mode via shooting technique. The shooting method was adapted with the Newton divided difference interpolation approach as the strategy of seeking for the new initial estimate. Five numerical examples are included to examine and illustrate the practical usefulness of the proposed method. Numerical tested problem is also highlighted on the diffusion of heat generated application that imposed the Robin boundary conditions. The present findings revealed that the proposed method gives an efficient performance in terms of accuracy, total function calls, and execution time as compared with the existing method.